Connecting the Person by Removing the Stigma: Why Ireland Should Follow the Portuguese Model of Drug Decriminalisation - Finucane, Aisling; Moran Stritch, Jennifer (South Eastern European Journal of Public Health (SEEJPH), 2022)
The decriminalisation of drugs and how it can impact addiction, crime and mental health is a subject that inspires global interest and debate. Much has been written about the positive outcomes of decriminalisation from a public health perspective, including the elimination of aggressive policing and community oversight and the shift to offering treatment and social supports for those affected by addiction. Ireland has yet to move to a model of decriminalisation, although a system similar to the one employed in Portugal has been suggested. This article briefly outlines reasons why a paradigm shift is vital if progress is to be made in reducing addiction in contemporary Ireland. The potential benefits could include a reduction in the pervasive social stigma connected with substance abuse, leading to less social exclusion within the Irish population.